Pengaruh Pembiayaan Mudharabah dan Tabungan Wadiah Terhadap Profitabilitas Bank Syariah di Indonesia - Ami Nullah Marlis Tanjung (AGHNIYA : Jurnal Ekonomi Islam, 2022)
This research is a quantitative study, to see the effect of mudharabah financing and wadiah savings on profitability, in this case profitability is represented by Retrun On Asset. The results obtained that partially, mudharabah affects Retrun On Asset as seen from the t count t table (8,5111,663) and a significant level smaller than 0.05 (0.0020.05).  Wadiah savings affect ROA  as seen from the t count t table (4,2431,663) and a significant level smaller than 0.05 (0.0030.05).  Meanwhile, simultaneously, mudharabah financing and wadian savings affect Retrun On Asset in Islamic banks in Indonesia, amounting to 82.0%.